Combined extractives of red yeast rice, bitter gourd, chlorella, soy protein, and licorice improve total cholesterol, low-density lipoprotein cholesterol, and triglyceride in subjects with metabolic syndrome - Lee, I-Te; Lee, Wen-Jane; Tsai, Ching-Min; Su, Ih-Jen; Yen, Hsien-Tung; Sheu, Wayne H-H. (Nutrition research (New York, N.Y.), 2012)
In this study, we aimed to examine the effects of a plant-extractive compound on lipid profiles in subjects with metabolic syndrome. We hypothesized that extractives from red yeast rice, bitter gourd, chlorella, soy protein, and licorice have synergistic benefits on cholesterol and metabolic syndrome. In this double-blinded study, adult subjects with metabolic syndrome were randomized to receive a plant-extractive compound or a placebo treatment for 12 weeks. Both total cholesterol (5.4 ± 0.8 to 4.4 ± 0.6 mmol/L, P < .001) and low-density lipoprotein cholesterol (3.4 ± 0.7 to 2.7 ± 0.5 mmol/L, P < .001) were significantly reduced after treatment with the plant extractives, and the magnitudes of reduction were significantly greater than in the placebo group (−1.0 ± 0.6 vs 0.0 ± 0.6mmol/L, P < .001; −0.7 ± 0.6 vs 0.0 ± 0.6 mmol/L, P < .001). The reduction in the fasting triglycerides level was significantly greater in the plant-extractive group than in the placebo group (−0.5 ± 0.8 vs −0.2 ± 1.0 mmol/L, P = .039). There was also a significantly greater reduction in the proportion of subjects with hypertensive criteria in the plant-extractive group than in the placebo group (P = .040). In conclusion, the plant extractives from red yeast rice, bitter gourd, chlorella, soy protein, and licorice were effective in reducing total and low-density lipoprotein cholesterol. The plant extractives also showed potential for reducing triglyceride and normalizing blood pressure.